Determinants of innovation in developing countries: a panel Generalized Method of Moments analysis - Nurnaddia Nordin,; Nurhaiza Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study aims to examine empirically the determinants of innovation in developing countries by using 52 selected countries with data spanning from 2000 to 2010. Innovation, defined as a process that attempts to try out new or improved products and processes. In order to achieve this phase, past studies have emphasized the determinants of innovation as human capital, patent, trademark, regulation, stock market, and trade openness. A systematic empirical study based on the Generalized Method of Moments (GMM) which has been taken to estimate all these determinants of innovation discussed by researchers in capturing the long-run and short-run relationship. This paper answers the question, “Among the determinants of innovation, which factor will be the main determinant and contributes to the success of innovation?” The result addressed that trade openness has played a significant and important role as a determinant of innovation in developing countries and surprisingly our results indicate that the stock market and trademark showed a negative impact on innovation. In line with past researchers, trade openness is one of the framework conditions that will improve, enhance and strengthen innovation in developing countries.